Applying SMED methodology in cork stoppers production - Sousa, E. (2020)
Organizations are increasingly required to have a high level of quality and flexibility in production. In order to remain in the market and become competitive, the working methods practiced must be reliable and efficient. The present project sought the improvement of an equipment of the cork industry by introducing a variation, through the application of Lean methods. The equipment under study performs the union of a cork stopper to a capsule, which is done by gluing it with hot-melt glue. The amount of production makes the changeover activity a regular process. The method followed in this work was the study and collection of information on the Lean production philosophy and its application in the cork industry. The working conditions of the assembly machine were also analyzed in order to find opportunities for improvement. Thus, the tool used was the Value Stream Mapping (VSM) technique in order to acknowledge the processes that really add value to the product. The SMED (Single Minute of Exchange of Die) methodology was applied in a way to reduce the downtime caused by tool changes, and a reduction of 43% in total changeover time was obtained. It was also created an A3 model to monitor the entire development of the SMED project, Finally, the OEE (Overall Equipment Efficiency) calculation was implemented as an indicator of overall equipment efficiency, in order to improve the monitoring of possible deviations during production. The feedback also proves that lean tools are a powerful method to get solid returns without large investments.